Brazil Hosting of the 2024 G20: Promise and Impediments in a High-Stakes, High-Drama Summit - F. Cooper, Andrew F. Cooper (CEBRI-Revista: Brazilian Journal of International Affairs, 2024)
This article offers an appraisal of both the promise and impediments regarding Brazil's hosting of the 2024 G20, a high-stakes, high-drama event. President Lula da Silva–with capable bureaucratic support–possesses both strong elements of charisma and experience that play well to the space of performance and policy. Nevertheless, at both the state and societal level, complications obtrude. Building popular support for the G20 faces the constraints of political and societal divisions. Furthermore, notwithstanding hopes that Brazil (and Lula) will be able to promote an expansive policy agenda, expectations persist that a turn back to geopolitical considerations will dominate the summit.